2023
DOI: 10.1158/2767-9764.crc-23-0165
|View full text |Cite
|
Sign up to set email alerts
|

Population-specific Mutation Patterns in Breast Tumors from African American, European American, and Kenyan Patients

Wei Tang,
Flora Zhang,
Jung S. Byun
et al.

Abstract: Women of African descent have the highest breast cancer mortality in the United States and are more likely than women from other population groups to develop an aggressive disease. It remains uncertain to what extent breast cancer in Africa is reminiscent of breast cancer in African American or European American patients. Here, we performed whole-exome sequencing of genomic DNA from 191 breast tumor and non-cancerous adjacent tissue pairs obtained from 97 African American, 69 European American, 2 Asian America… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 58 publications
0
0
0
Order By: Relevance
“…In contrast to most populations where TP53, PIK3CA and GATA3 are the most mutated genes (Pan et al, 2020;Pipek et al, 2023;Tang et al, 2023), in our study population, three genes MUC16, MUC17 and TTN were highly mutated in over 50% of the samples and produced the highest number of neoantigens. MUC16 has been reported to take part in breast cancer progression and metastasis when overexpressed due to its influence on cell cycle and survival through the JAK2/STAT3 pathway (Lakshmanan et al, 2012).…”
Section: Discussioncontrasting
confidence: 94%
See 3 more Smart Citations
“…In contrast to most populations where TP53, PIK3CA and GATA3 are the most mutated genes (Pan et al, 2020;Pipek et al, 2023;Tang et al, 2023), in our study population, three genes MUC16, MUC17 and TTN were highly mutated in over 50% of the samples and produced the highest number of neoantigens. MUC16 has been reported to take part in breast cancer progression and metastasis when overexpressed due to its influence on cell cycle and survival through the JAK2/STAT3 pathway (Lakshmanan et al, 2012).…”
Section: Discussioncontrasting
confidence: 94%
“…Although most of the top 10 mutated genes (80%) were also the top 10 in the number of neoantigens generated, genes like TP53 and PIK3CA that are reported to be highly mutated in most patient cohorts were not among the top 10 mutated genes in this study, but generated among the highest number of neoantigens (Figure 6; Figure 7). ARID1A gene, which showed unique mutational profile in Kenyan population using exome data compared to African American and Asian population (Tang et al, 2023), was not among the highly mutated, but produced neoantigens. We found that most neoantigens were derived predominantly from missense mutations (88%), compared to indels and frameshift mutations (12%).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations